Find an acute angle θ when cosθ - sinθ/cosθ + sinθ = 1+ √3/1 + √3
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
CBSE Class 10 Sample Paper for 2023 Boards - Maths Standard
Question 2 Important
Question 3 Important
Question 4 Important
Question 5
Question 6 Important
Question 7
Question 8 Important
Question 9
Question 10 Important
Question 11 Important
Question 12
Question 13 Important
Question 14 Important
Question 15
Question 16 Important
Question 17
Question 18 Important
Question 19 [Assertion Reasoning] Important
Question 20 [Assertion Reasoning] Important
Question 21 Important
Question 22
Question 23 Important
Question 24 (Choice 1)
Question 24 (Choice 2)
Question 25 (Choice 1)
Question 25 (Choice 2) Important You are here
Question 26
Question 27 Important
Question 28 (Choice 1) Important
Question 28 (Choice 2)
Question 29 Important
Question 30 (Choice 1)
Question 30 (Choice 2) Important
Question 31
Question 32 (Choice 1) Important
Question 32 (Choice 2)
Question 33 Important
Question 34 (Choice 1)
Question 34 (Choice 2) Important
Question 35
Question 36 (i) [Case Based] Important
Question 36 (ii) Important
Question 36 (iii) (Choice 1)
Question 36 (iii) (Choice 2)
Question 37 (i) [Case Based] Important
Question 37 (ii) (Choice 1) Important
Question 37 (ii) (Choice 2)
Question 37 (iii)
Question 38 (i) [Case Based] Important
Question 38 (ii) (Choice 1)
Question 38 (ii) (Choice 2) Important
Question 38 (iii)
CBSE Class 10 Sample Paper for 2023 Boards - Maths Standard
Last updated at May 29, 2023 by Teachoo
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
Question 25 (Choice 2) Find an acute angle θ when (cosθ − sinθ)/(cosθ + sinθ ) = (1 − √3)/(1 + √3)Given (cosθ − sinθ)/(cosθ + sinθ ) = (1 − √3)/(1 + √3) Cross multiplying (1 + √3) (cos θ − sin θ) = (1 − √3) (cos θ + sin θ) 1 (cos θ − sin θ) + √3(cos θ − sin θ) = 1 (cos θ + sin θ) − √3 (cos θ + sin θ) cos θ − sin θ + √3cos θ − √𝟑 sin θ = cos θ + sin θ − √3cos θ − √𝟑sin θ − sin θ + √3cos θ = sin θ − √3cos θ √3cos θ + √3cos θ = sin θ + sin θ 2√𝟑cos θ = 2 sin θ √3cos θ = sin θ √3 = sin〖θ 〗/cos〖θ 〗 tan θ = √3 Since tan 60° = (cosθ − sinθ)/(cosθ + sinθ ) = (1 − √3)/ So, the correct answer is (c) √3 = sin〖θ 〗/cos〖θ 〗 tan θ = √𝟑 Since tan 60° = √3 Therefore, θ = 60°